نکاح مسیار اور شریعت کا اصول مصلحت: The Misyar marriage and the principle of Islamic jurisprudence "Maslaha" - Mehr Din; Dr. Muhammad Saad Siddiqui (jihat-ul-islam, 2020)
The Misyar marriage is legal across Arab countries. It is a contract under which the husband and wife give up several rights by their own free will, such as living together, equal division of nights between wives, the wife's rights to housing and maintenance money and the husband's right to home keeping and excess etc. The reasons that have led to the emergence of this kind of marriage are many such as: increase in the number of single women who are unable to get married, some women need to stay in their family home, some married man want to keep some women chaste because they need that, in some cases a husband may want to conceal his second marriage from his first wife, the man travels a phone to a certain place and stays there for lengthy periods so staying there with a wife is safer for him than not doing so. The scholars differed concerning the ruling on this type of marriage, and there are several opinions, ranking from the view that it is permissible, to the view that it is permitted but makrooh, or that it is not allowed. This article is an attempt to highlight the concept of the Misyar marriage in the light of the Islamic jurisprudence. The result of this research is that if the Misyar marriage fulfills the conditions of a valid marriage, namely the proposal and acceptance. The consent of the wali and witnesses or announcement of the marriage, then it is a valid marriage contract and it is good for some categories of men and women whose circumstances call for this type of marriage.